Living donor liver transplantation in septuagenarians: Better late than never. Issue 6 (13th April 2021) - Zidan, Ahmed; Sturdevant, Mark; Elsarawy, Ahmed; Hassan, Ramy; Alabbad, Saleh; Alghamdi, Saad; Bzeizi, Khalid; Broering, Dieter C.
Abstract: Background: The coupling of increased life expectancy and improvements in both quality and access to chronic liver disease care, is culminating in an expanding population of septuagenarians (≥70 years) in need of liver transplantation (LT). The objective of this study is to partially alleviate this knowledge deficit and to add clarity to the current status and role of LDLT in this recipient population. Methods: Of 295 adult patients underwent LDLT between January 1, 2011 and December 31, 2016. Twelve (4%) of these patients were septuagenarians and this group was compared to younger cohort ( n = 283). Results: Comorbidity profiles between the two groups were similar and no statistically significant differences were noted in warm/cold ischemia times, operative duration, or blood product utilization. ICU and total hospital stays were comparable. Septuagenarian 1‐and 5‐year graft and patient survivals were identical at 91.7%. Their younger counterparts had 1‐and 5‐year patient survivals of 91.1% and 84.0 % accompanied by 1‐and 5‐year graft survivals of 89.8% and 82.7%, respectively. Conclusion: Our study highlights a recognition that LDLT can afford highly‐selected elderly patients to access to transplant with equivalent outcomes to those realized by younger recipients.